Effect of wounding and wound age on infection of canola cotyledons by Leptosphaeria maculans, interacting with leaf wetness. Issue 5 (3rd September 2022) - Huang, Shuanglong; Zhai, Chun; Zou, Zhongwei; Liu, Fei; Parks, Paula; Mcgregor, Linda; Fernando, W. G. Dilantha; Peng, Gary
Abstract: Blackleg, caused by the fungus Leptosphaeria maculans, is an important disease of canola. Both ascospores and pycnidiospores of the fungus can infect intact leaves under conditions of extended leaf wetness, with infection then progressing further into the stem. In western Canada, spring is typically cool and dry and additional factors may be involved for successful infection. This study was designed to assess the effect of wounding and wound age on cotyledon infection, to evaluate the likelihood that flea beetle-feeding injuries could contribute to increased disease. Infection of canola cotyledons occurred readily via mechanical wounds in the absence of leaf wetness when seedlings were spray inoculated with pycnidiospores of L. maculans, whereas no infection occurred on intact cotyledons even under 6-h leaf wetness. Wound age also played a role in susceptibility; wounded tissues were less susceptible when plants were kept in a greenhouse for 8 h or longer before inoculation, with substantially reduced infection success relative to fresh wounds. This wound-age effect was similar on susceptible and resistant canola varieties. A high temperature (25°C) seemed to favour the healing of wounds, reducing susceptibility when compared with control (21/16°C) and low (10°C) temperatures. Leaf wetness post-wounding may hinder healing, and high post-inoculation humidity (80–90% relative humidity) increased infection via older wounds slightly, relative to lower (50–60%) relative humidity. These data provide a rationale for studying the effect of improved flea beetle control on early L. maculans infection of canola.